2020
DOI: 10.1109/access.2020.2966656
|View full text |Cite
|
Sign up to set email alerts
|

SMSH: Secure Surveillance Mechanism on Smart Healthcare IoT System With Probabilistic Image Encryption

Abstract: The Internet of Things is made of diverse networked things (i.e., smart, intelligent devices) that are consistently interconnected, producing meaningful data across the network without human interaction. Nowadays, the Healthcare system is widely interconnected with IoT environments to facilitate the best possible patient monitoring, efficient diagnosis, and timely operate with existing diseases towards the patients. Concerning the security and privacy of the patient's information. This paper is focused on Secu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 50 publications
(88 reference statements)
0
24
0
Order By: Relevance
“…This paper has both theoretical implications for the cybersecurity literature and practical implications for IT managers. First, the existing cybersecurity literature mainly focuses on: (i) individual solutions to improve the automatic detection system [ 21 , 22 , 61 ]; (ii) presentation of cybersecurity architecture and standards [ 23 , 62 , 63 ], and (iii) development of algorithms for medical image encryption [ 64 , 65 , 66 ]. Therefore, despite the existence of many studies on cybersecurity, this study provides theoretical contributions to cybersecurity literature because it is the first paper that incorporates a qualitative–quantitative methodological approach designed for medical image security.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…This paper has both theoretical implications for the cybersecurity literature and practical implications for IT managers. First, the existing cybersecurity literature mainly focuses on: (i) individual solutions to improve the automatic detection system [ 21 , 22 , 61 ]; (ii) presentation of cybersecurity architecture and standards [ 23 , 62 , 63 ], and (iii) development of algorithms for medical image encryption [ 64 , 65 , 66 ]. Therefore, despite the existence of many studies on cybersecurity, this study provides theoretical contributions to cybersecurity literature because it is the first paper that incorporates a qualitative–quantitative methodological approach designed for medical image security.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…This type of multi-network model paves the way for attaining the best performance at minimum training time. But if a multi-model is used, then characteristics of the network should be defined sensibly and if any error is made during implementation, then entire network performance will be degraded [16][17][18].Additionally, recent literature [19][20][21][22][23] have also demonstrated that automatic detection of COVID is possible using different methods like neural network, X-ray images, radiography, deep learning and image encryption. Therefore, by considering the aforementioned concepts in cognizance a new method of COVID detection using block chain technology has been implemented in the proposed method.…”
Section: Literature Surveymentioning
confidence: 99%
“…In the field of cloud security, Identity management plays an important role. Privacy as well as compatibility are the major problems with current solutions to identity management, particularly in public cloud environments [10], [11], [18]. Currently, IAM systems are effective mechanisms for reducing cloud-based risks.…”
Section: Preliminariesmentioning
confidence: 99%
“…The flow of communication within the organization and outside is inviting many security and privacy challenges among the user. The restriction of the adversarial attack is highly required and build such type of mechanism which can deal to provide a framework and use proper access among the authorized user [9]- [11]. To ensuring such type of mechanism our intension to encourage to develop an essential tool or any type of integration approach, concerning these technological enhancements, this article is going to optimized with the integration of the identity access management framework (IAM) and privileged access management (PAM) as an active directory which is demonstrated on the Fig 1 . The architecture of the system incorporates as a managerial way such as life cycle manager, compliance manager, password manager and the layout of the system demonstrated such as identity intelligence, dashboards, reporting console, analysis console.…”
Section: Introductionmentioning
confidence: 99%